Coffee Landscape of Banyuwangi Geopark: Ecology, Conservation, and Sustainable Tourism Development - Luchman Hakim; Brian Rahardi; Dodit Ari Guntoro; Naila Izzatul Mukhoyyaroh (Journal of Tropical Life Science, 2022)
Coffee landscape is one of the crucial elemnt of Banyuwangi Geopark, East Java. Coffee landscape plays an essential role in supporting the sustainable ecosystem in Banyuwangi Geopark. A number of studies have already examined ways to develop and preserve the coffee landscape and its biodiversity, especially in coffee cultivated under agroforestry system. This paper aims to describe the ecology of coffee landscapes in Banyuwangi, identify the problems and opportunities for preservation and biodiversity conservation, explore the possibilities of integrating coffee and tourism, and provide recommendations to preserve the coffee landscape and its biodiversity. Field survey, literature studies and interviews with farmers, tourism consultants, local travel planner, and local guides were conducted to get comprehensive data and information of the tourism potential of coffee landscape ecosystems. Data were analyzed using descriptive analysis. Result of the study shows that Banyuwangi is home to numerous state-, private-, and peasant-owned coffee orchards. Coffee agroforestry has already been established for a long time, contributing to biodiversity conservations. Coffee cultivation is a common practice among communities, which later inspired the creation of a coffee festival. With the high number of tourism attractions located in the geopark area coupled with the trend in tourism development, there is potential in integrating coffee into tourism. Important actions have to be done first, and these are as follows: mapping and describing coffee orchard distribution, enhancing peasant capacity in coffee cultivation, introducing and strengthening sustainable tourism principles, and establishing regulation to ensure the preservation and conservation of coffee cultural landscapes. Result of the studies reported here can be used to provide guidelines for the management of coffee landscape in the BanyuwangiÃ‚Â Geopark area.